Identifikasi Stabilitas Lereng Tanah Longsor Menggunakan Metode Elemen Hingga - Alfadhella Ridwan Fadhel; Muhardi; Muhammad Yusa (Jurnal Teknik, 2019)
Landslide is one of the disasters that has a high level of damage. This research aims to identify slope stability which was modeled by using a based finite element method software, i.e. Plaxis V.8.2. The data that were used are slope dimension, material properties, and reinforcement properties. These data were used as input in modeling. The slope was modeled in the condition before the reinforcement and after the reinforcement. The reinforcement was given on the slope by using piles and retaining wall. The results showed that the safety factor before reinforcement is 1,19 and after reinforcement is 1,48. The results also shown that the displacements after reinforcement was lower than before reinforcement. This proves that the slope reinforcement was able to increase the safety factors and reduce the displacements on the slope